2018
DOI: 10.1002/aur.1930
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Spontaneous Visual Attention in Children on the Autism Spectrum: A Proof‐of‐Concept Study Comparing Singing and Speech

Abstract: Children on the autism spectrum may have difficulty looking at people, particularly their faces. In this study, children watched videos of someone singing or reading a story. The results show that children look more at the person if they were singing and if the story was familiar to them. Using songs and familiar stories may be a way to help children with autism to naturally engage with others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Music therapy can include various forms of music‐making, especially singing, because vocal melodies are more memorable than other melodies, as shown here and elsewhere, and because they are inherently engaging [Weiss et al, 2016]. Other research has shown a greater degree of socio‐communicative engagement for sung words than for spoken words in children with ASD [Paul et al, 2015; Thompson & Abel, 2018]. In short, we recommend the inclusion of vocal music in therapeutic interventions, where feasible, rather than assuming that voice processing difficulties in nonmusical contexts preclude productive use of the voice in musical contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Music therapy can include various forms of music‐making, especially singing, because vocal melodies are more memorable than other melodies, as shown here and elsewhere, and because they are inherently engaging [Weiss et al, 2016]. Other research has shown a greater degree of socio‐communicative engagement for sung words than for spoken words in children with ASD [Paul et al, 2015; Thompson & Abel, 2018]. In short, we recommend the inclusion of vocal music in therapeutic interventions, where feasible, rather than assuming that voice processing difficulties in nonmusical contexts preclude productive use of the voice in musical contexts.…”
Section: Discussionmentioning
confidence: 99%
“…For individuals with ASD, impaired processing of vocalizations and typical or enhanced processing of nonvocal music make their processing of vocal music of particular interest. When language is sung rather than spoken, it elicits greater engagement [Paul et al, 2015; Simpson, Keen, & Lamb, 2013; Thompson & Abel, 2018] and more typical patterns of fronto‐temporal connectivity [Lai, Pantazatos, Schneider, & Hirsch, 2012; Sharda, Midha, Malik, Mukerji, & Singh, 2015] in individuals with ASD. These findings imply that atypical processing of vocalizations is limited to speech and other nonmusical contexts or that music engages a distinctive mode of processing in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Eye-tracking studies measuring gaze toward social target areas in still pictures ( 22 ), videos ( 23 ), or in vivo social interactions using computer applications ( 24 ) have revealed notable differences in individuals with autism. Thompson et al reported that ASD children have difficulty looking at people, particularly their faces, but when they watched videos of someone singing or reading a story, they would look more at the person if they were singing and if the story was familiar to them; thus, using songs and familiar stories may be a way to help children with autism to naturally engage with others ( 25 ). Similar studies have shown that music can be used to improve emotion recognition in facial expressions and emotion induction through facial stimulation in children with high functioning ASDs ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Visual music therapy using songs and familiar stories can enhance ASD children's attention, help ASD children pay more attention to their faces, and promote ASD children to participate in social interaction more naturally and spontaneously. It is to help ASD children in a natural situation An effective way to interact with others [15] .…”
Section: Attentionmentioning
confidence: 99%